Dilated cardiomyopathy and pregnancy outcome: a case report - Jimo, Kanili; Liegise, Avitso; Moses, Adahru; Jamir, Bendangtoshi; Momin, Rebeki; Thapa, Vivek (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Cardiomyopathy is a group of diseases that affect the heart muscle. Dilated cardiomyopathy, a form of cardiomyopathy, is characterised by ventricular chamber enlargement and contractile dysfunction, and has recurrences in subsequent pregnancies. Pregnancy by itself is associated with significant hemodynamic burden and cardiovascular changes, which when coupled with dilated cardiomyopathy results in increased morbidity and mortality in both mother and child. Management of such a condition presents serious therapeutic challenge to a multidisciplinary team. Here, we report a case of a 36-year-old woman primigravida with gestational age of 11 weeks, known case of dilated cardiomyopathy. Despite the risks and associated complications with the disease, she continued her pregnancy. Patient was managed by a team of obstetrician, cardiologist and anaesthesiologist and underwent caesarean section giving birth to a live baby. The aim of this article is to provide guidance on how to manage a patient with dilated cardiomyopathy throughout her pregnancy. Early diagnosis of heart disease, regular antenatal check-ups, institutional delivery and multidisciplinary approach can reduce the maternal and perinatal morbidity and mortality.